2004
DOI: 10.2118/04-04-01
|View full text |Cite
|
Sign up to set email alerts
|

Network Modelling of Apparent-Relative Permeability of Gas in Heavy Oils

Abstract: FIGURE 1: Schematic representation of bubble movement from (a) to (c). The right hand side depictions correspond to schematic representations of a network model.FIGURE 2: A typical branch in a unit cell (UC) of the porous medium model [Modified from Reference (9)]. FIGURE 3: Depiction of a 4-UC bubble. A branch (BR), a gate branch (GBR), a unit cell (UC), and periodicity length (l) are shown on the sketch [Modified from Reference (9)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, in heavy oil systems, the oil viscosity has also been found to affect the gas relative permeability. Talabi et al, (2003) and Javadpour et al, (2004) suggested that, in heavy oil systems, the gas relative permeability decreases with increasing oil viscosity. As a similar implication, Li et al (2016) presented that the gas relative permeability increased distinctly with temperature -the change in temperature accompanied a variation in oil viscosity.…”
Section: Solution Gas Drivementioning
confidence: 99%
“…However, in heavy oil systems, the oil viscosity has also been found to affect the gas relative permeability. Talabi et al, (2003) and Javadpour et al, (2004) suggested that, in heavy oil systems, the gas relative permeability decreases with increasing oil viscosity. As a similar implication, Li et al (2016) presented that the gas relative permeability increased distinctly with temperature -the change in temperature accompanied a variation in oil viscosity.…”
Section: Solution Gas Drivementioning
confidence: 99%
“…In a field model, Bayon et al reported an oil recovery factor ranging from 25–35 % with a depressurization rate of 80–800 kPa/day. Other researchers have studied foamy solution gas drives and concluded the oil recovery is in the ranges of 5–25 % and > 10 % . However, these studies have not established pseudo‐reaction modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have studied foamy solution gas drives and concluded the oil recovery is in the ranges of 5-25 % [7] and > 10 %. [8] However, these studies have not established pseudo-reaction modelling.…”
Section: Introductionmentioning
confidence: 99%
“…In the field model, Bayon et al [6] reported the oil recovery factor was in range from 25 to 35% with depressurization rate from 80 to 800 kPa/day. Other researchers have studied foamy solution gas drives and concluded the oil recovery is in range 5 to 25% [7] and higher than 10% [8].…”
Section: Introductionmentioning
confidence: 99%